Kampung Kubur Menjadi Kampung Sejahtera: Habituasi sebagai Pondasi untuk Mencapai Perubahan Sosial - Yusepa, Irda; Jahiddin, Ismail; Selvianti, Rivie; Siregar, Izuddinsyah; Lionar, Uun; Mhd Ricky Ardiansyah putra; Mhd Ricky Ardiansyah putra (Jurusan Sejarah FIS UNP, 2025)
Kampung Kubur in Medan City has long been known as a marginalized area with negative stigmas related to crime, drug trafficking, and slum conditions. This stigma not only impacts the village’s image but also impacts the social and economic access of its residents. This study aims to analyze the forms of social change that have occurred in Kampung Kubur following government and security force interventions and active community participation in transforming the area into a Prosperous Village. The research method used is a descriptive qualitative approach, with data collection techniques including field observations, in-depth interviews with residents and relevant officials, and document analysis. The results indicate that changes include improvements to the physical environment, increased security, and the emergence of more positive social interaction patterns among residents. Programs such as the Tobat Berobat (Repentance Post), cooperation activities, and the revitalization of public spaces have been proven to improve the community’s quality of life. Although challenges related to old stigmas and economic conditions persist, the community demonstrates strong adaptability and a collective commitment to building a new identity as a safe, clean, and empowered village.